Use of code-switching in multilingual content subject and language classrooms - Gwee, Susan; Saravanan, Vanithamani (International journal of multilingualism, 2018)
Research literature has shown that teachers code-switched to a language which is not the medium of instruction to help students understand subject matter and establish interpersonal relations with them. However, little is known about the extent to which teachers code-switch in content subject classrooms compared to language classrooms. Using substantial data taken from a larger study, this paper examined the extent to which teachers code-switched in both content subject and language Grade 5 multilingual classrooms in Singapore and the code-switching functions used. The data for this study accounted for 23.6% of the lessons observed in the larger study and comprised 91 transcripts of science, mathematics, social studies, and English lessons. The data from the transcripts were tagged for the analysis of teachers' use of the non-standard English dialect, Singapore Colloquial English, for the broad functions of curriculum access, classroom management, and interpersonal relations and their sub-functions. Grade 5 teachers were found to use the non-standard English dialect more often for curriculum access than for classroom management. Content subject teachers code-switched more frequently than language teachers.